PENGEMBANGAN BAHAN AJAR IPAS BERBASIS BUDAYA LOKAL PADA SDN 36 PONTIANAK SELATAN - Putri, Helpina; Hairida; Ghasya, Dyoty Auliya Vilda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning is less contextual, so students are less able to relate the material to their daily lives. This study aims to develop local culture-based science teaching materials at SDN 36 Pontianak Selatan through the ADDIE model development research. The analysis stage conducted a preliminary study to explore the problems that occur in science teaching in elementary schools. The design stage carried out development planning by creating a storyboard and a simple framework for teaching materials. The development stage was carried out by realizing the design framework into a finished product while providing validation of the product related to the material, appearance, and language aspects. Validation of the material, appearance, and language aspects showed a percentage above 90, with an average of 92%, 91%, and 90%, respectively. Product revisions were carried out before the product was truly declared suitable for use in elementary schools. In conclusion, local culture-based teaching materials at SDN 36 Pontianak Selatan were declared suitable for use in schools because they can improve the quality of learning and help students understand science concepts meaningfully and deeply.